Sphingolipid metabolites involved in the pathogenesis of atherosclerosis: perspectives on sphingolipids in atherosclerosis - Fufangyu Zhao; Mingyan Shao; Mingrui Li; Tianxing Li; Yanfei Zheng; Wenlong Sun; Cheng Ni; Lingru Li (Cellular & Molecular Biology Letters)
Abstract Atherosclerosis, with its complex pathogenesis, is a leading underlying cause of many cardiovascular diseases, which are increasingly prevalent in the population. Sphingolipids play an important role in the development of atherosclerosis. Key metabolites and enzymes in sphingolipid metabolism influence the pathogenesis of atherosclerosis in a variety of ways, including inflammatory responses and oxidative stress. Thus, an investigation of sphingolipid metabolism-related metabolites and key enzymes may provide novel insights and treatment targets for atherosclerosis. This review discusses various mechanisms and research progress on the relationship between various sphingolipid metabolites, related enzymes, and atherosclerosis. Finally, we look into the future research direction of phytosphingolipids. Graphical Abstract